2020
DOI: 10.1002/14651858.cd013128.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for chronic pruritus of unknown origin

Abstract: Interventions for chronic pruritus of unknown origin (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 183 publications
(71 reference statements)
0
25
0
2
Order By: Relevance
“…The term ‘chronic pruritus of unknown origin’ (CPUO) (previously known as chronic idiopathic pruritus or pruritus sine materia ) was proposed to define this condition, whose diagnosis is made by exclusion [ 112 ]. CPUO might be localized or generalized, with increased prevalence (from 3.6 to 44.5%) among middle- to old-aged subjects [ 112 , 113 ]. Elderly patients are at an increased risk of CP due to the cumulative effects of aging on the skin barrier and neurotrophic function.…”
Section: The Top Itchy Skin Diseasesmentioning
confidence: 99%
“…The term ‘chronic pruritus of unknown origin’ (CPUO) (previously known as chronic idiopathic pruritus or pruritus sine materia ) was proposed to define this condition, whose diagnosis is made by exclusion [ 112 ]. CPUO might be localized or generalized, with increased prevalence (from 3.6 to 44.5%) among middle- to old-aged subjects [ 112 , 113 ]. Elderly patients are at an increased risk of CP due to the cumulative effects of aging on the skin barrier and neurotrophic function.…”
Section: The Top Itchy Skin Diseasesmentioning
confidence: 99%
“…Clinical trials to evaluate serlopitant as a potential therapeutic for AD to reduce itching and pruritus indicated that serlopitant was capable to reduce the pruritus associated with AD. However, the results were not statistically significant, and further studies are required to establish clinical significance [202,203]. Tradipitant (VLY-686) is a small molecule inhibitor of the NK1 receptor that blocks this receptor and prevents interaction with its ligand, substance P (SP), which is released on activation of sensory neurons.…”
Section: Emerging Therapeutic Small Molecules For Admentioning
confidence: 99%
“…Both the transformation models can be considered as references when conducting related studies in the future. One Cochrane review on chronic pruritus of unknown origin included studies with different assessment tools to measure the same outcome, using standardized mean differences (SMDs) with 95% CIs to analyze the continuous data [45]. Therefore, we performed data synthesis and analysis with SMDs to analyze different pruritus scores in our study.…”
Section: Outcome Measurementsmentioning
confidence: 99%